Menthol as an Adjuvant to Help Athletes Cope With a Tropical Climate: Tracks From Heat Experiments With Special Focus on Guadeloupe Investigations - Hue, Olivier; Chabert, Clovis; Collado, Aurélie; Hermand, Eric (Frontiers in Physiology, 2019)
Endurance and prolonged exercise are altered by hot climate. In hot and dry climate, thermoregulation processes, including evapotranspiration, normally maintain a relatively constant body core temperature. In hot and wet climate (usually called “tropical”), the decrease in evapotranspiration efficacy increases the sweating rate, which can rapidly induce severe hypohydration without efficiently reducing core temperature. The negative effects of tropical environment on long-duration exercise have been well documented, with clear demonstrations that they exceed the acclimation possibilities: both acclimated athletes and natives to tropical climate show impaired performances compared with that in neutral climate. New countermeasures, applicable during competitive events, are therefore needed to limit these negative effects. We studied the effects of several countermeasures in outdoor or natural tropical climates and noted that the easiest method to apply is cooling with cold (-1 to 3°C) beverage. Moreover, adding menthol increased the cold sensation induced by the beverage temperature, optimizing the positive effects on performance. We also demonstrated that efficient pre-cooling with cold menthol beverage requires drinking for 1 hour instead of 30 minutes before the exercise. The optimal cooling method seems to be 1 hour of cold+menthol pre-cooling ingestion followed by menthol+ice-slurry per-cooling. However, limitations should be noted: a) the menthol concentration seems to be crucial, with positive effects for a 0.05% solution, whereas higher concentrations need to be explored; and b) because it acts as a cold adjuvant without decreasing core temperature, menthol can lead to decreased thermoregulatory processes, thus inducing hyperthermia. Last, if menthol is added to cooling processes, athletes should first test them in training conditions for the maximal cooling effect to ensure optimal performance in competition in tropical climate.